Clinical Use of High-Intensity Focused Ultrasound (HIFU) for Tumor and Pain Reduction in Advanced Pancreatic Cancer - Strunk, H. M.; Henseler, J.; Rauch, M.; Mücke, M.; Kukuk, G.; Cuhls, H.; Radbruch, L.; Zhang, L.; Schild, H. H.; Marinova, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: Evaluation of ultrasound-guided high-intensity focused ultrasound (HIFU) used for the first time in Germany in patients with inoperable pancreatic cancer for reduction of tumor volume and relief of tumor-associated pain.Materials and Methods: 15 patients with locally advanced inoperable pancreatic cancer and tumor-related pain symptoms were treated by HIFU (n = 6 UICC stage III, n = 9 UICC stage IV). 13 patients underwent simultaneous standard chemotherapy. Ablation was performed using the JC HIFU system (Chongqing, China HAIFU Company) with an ultrasonic device for real-time imaging. Imaging follow-up (US, CT, MRI) and clinical assessment using validated questionnaires (NRS, BPI) was performed before and up to 15 months after HIFU.Results: Despite biliary or duodenal stents (4/15) and encasement of visceral vessels (15/15), HIFU treatment was performed successfully in all patients. Treatment time and sonication time were 111 min and 1103 s, respectively. The applied total energy was 386 768 J. After HIFU ablation, contrast-enhanced imaging showed devascularization of treated tumor regions with a significant average volume reduction of 63.8 % after 3 months. Considerable pain relief was achieved in 12 patients after HIFU (complete or partial pain reduction in 6 patients).Conclusion: US-guided HIFU with a suitable acoustic pathway can be used for local tumor control and relief of tumor-associated pain in patients with locally advanced pancreatic cancer.Key points:• US-guided HIFU allows an additive treatment of unresectable pancreatic cancer.• HIFU can be used for tumor volume reduction.• Using HIFU, a significant reduction of cancer-related pain was achieved.• HIFU provides clinical benefit in patients with pancreatic cancer.Citation Format:• Strunk HM, Henseler J, Rauch M et al. Clinical Use of High-Intensity Focused Ultrasound (HIFU) for Tumor and Pain Reduction in Advanced Pancreatic Cancer. Fortschr Röntgenstr 2016; 188: 662 – 670
Keywords: pancreatic carcinoma; high-intensity focused ultrasound; tumor ablation; pain relief; cancer pain